Hinduism an ancient path in the modern world - Henry, Oliver (Colorado : Delphi Production [production company] ; Evanston : United Learning [distributor], 1992)
This program traces the development of Hinduism from its inception to present day. Shot at numerous locations in India, it demystifies many of the concepts of the faith
Video is accompanied by 1 teacher's guide and 5 pages of blackline masters
Excepts from'The March of Time', courtesy of SFM Entertainment, a Division of SFM Media Corporation
Narrator, Keith Jackson
Keywords: Hinduism -- India; Hinduism -- History; Hinduism -- Rituals